POLA PERILAKU PENELUSURAN INFORMASI MAHASISWA DI ERA DIGITAL NATIVE - Latifa Hanum, Atiqa Nur (Universitas Tanjungpura, 2017)
Abstract Human behavior in searching different information but can establish a pattern that can be known the model search. In the case of this study, the focus is the behavior of students in searching information to meet the learning needs on campus. Exploratory research methodology with a quantitative approach. Collecting data through distributing questionnaires to 93 respondents to the survey technique as the primary data and conducting interviews as secondary data. Data analysis techniques performed by regression analysis model tiered or SEM (structural equation modeling) with Partial Least Square approach using tools SmartPls 2.0 and SPSS program to test for normality of data. The results showed that the characteristics of all respondents belonging to the Internet generation (net generation) or better known as a digital native with instant information search behavior patterns and digital in meeting information needs. Amounting to 68.82% of respondents chose the resources in the form of electronic media format as a medium of learning than the printed media. Amounting to 62.37% of respondents prefer to access information to support their learning tasks derived from internet and as much as 54.84% using the smartphone as a support tool accessing such information. In conclusion digital native generation tend to like information search patterns that come into contact with technology, is fast and easy, and like source of information in electronic media. Thus forming the pattern of searches ranging from needs information analysis (task/add insight) – environment (economic) - access location (internet/library) – selection (source of relevant information). Keywords: behavior, information retrieval, digital native